2015
DOI: 10.1177/1687814015592088
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of hydrodynamic performance of hydrofoils with leading-edge protuberances

Abstract: Leading-edge protuberances on airfoils or hydrofoils have been considered as a viable passive method for flow separation control recently. In this article, the hydrodynamic performance of a NACA 63 4 -021 (baseline) foil and two modified foils with leading-edge protuberances was numerically investigated using the Spalart-Allmaras turbulence model. It was found that modified foils performed worse than the baseline foil at pre-stall angles, while the lift coefficients at high angles of attack of the modified foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 22 publications
(57 reference statements)
1
19
0
1
Order By: Relevance
“…A pair of counter-rotating vortices stemming from the leading edge was considered to help keeping the flow attached to the suction surface, similar to the effect of a delta wing. The bi-periodic condition was verified through numerical simulation performed by Cai et al, and different modes of spanwise periodicity were discovered [12]. However, the formation mechanism of spanwise periodicity is still unclear, which needs further investigation.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A pair of counter-rotating vortices stemming from the leading edge was considered to help keeping the flow attached to the suction surface, similar to the effect of a delta wing. The bi-periodic condition was verified through numerical simulation performed by Cai et al, and different modes of spanwise periodicity were discovered [12]. However, the formation mechanism of spanwise periodicity is still unclear, which needs further investigation.…”
Section: Introductionmentioning
confidence: 82%
“…Most of the leading-edge protuberances were designed as continuous uniform distribution [7][8][9][10][11][12], and the flow patterns resulted from joint effects. In order to investigate the formation mechanism of spanwise periodicity, it is very necessary to examine the effect of a single protuberance, and further discuss the interferences of vortex structures between different protuberances.…”
Section: Introductionmentioning
confidence: 99%
“…Studies into its operation at low Reynolds numbers have spurred particular interests recently, due to their intriguing design characteristics and effects on flow separation behavior and vortex generation 2,3 . This research area draws its inspirations from the morphology of humpback whales which possess exceptional maneuvering and turning ability at higher velocities, especially when they are approaching their preys.…”
Section: Introductionmentioning
confidence: 99%
“…This research area draws its inspirations from the morphology of humpback whales which possess exceptional maneuvering and turning ability at higher velocities, especially when they are approaching their preys. It has been determined by earlier studies that the swiftness in the motion of a humpback whale is partially affected by the presence of pectoral flippers with leading-edge protuberances 3 . A detailed aerodynamic performance analysis of flippers with leading-edge protuberances was experimentally conducted by Miklosovic et al 4 at Re = 5 x 10 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is noted that there was only one tubercle wavelength considered in Cai et al, 12 Gross and Fasel 13 noted that this may not be appropriate if a bi-periodic pattern occurred. Cai et al 15 made further numerical investigations of the hydrodynamic performance of hydrofoils with leading-edge tubercles at Reynolds number 180,000. The results suggested that a sufficiently large spanwise width of the airfoil is required to gain a better description of flow patterns around the leading-edge protuberance.…”
Section: Introductionmentioning
confidence: 99%